2021
DOI: 10.3390/pathogens10091095
|View full text |Cite
|
Sign up to set email alerts
|

Natural Products and Their Potential Anti-HAV Activity

Abstract: The role of purified natural products in the prevention and treatment of countless diseases of bacterial, fungal, and viral origin cannot be overestimated. New antiviral drugs have been obtained from natural sources and transformed into preparations for prophylactic and therapeutic purposes. Flavonoids, polyphenols, saponins, proanthocyanins, polysaccharides, organic acids, proteins, polypeptides, and essential oils derived from plants, animals, or microorganisms can control and combat foodborne viral infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 108 publications
(141 reference statements)
0
4
0
Order By: Relevance
“…The available literature provides very limited information about the effect of different essential oils on HAV. Oils that have been previously studied include oregano, thyme, lemon, sweet orange, grapefruit, and rosemary [ 42 , 43 ]. However, there are no current studies on the effectiveness of EOCa against HAV.…”
Section: Resultsmentioning
confidence: 99%
“…The available literature provides very limited information about the effect of different essential oils on HAV. Oils that have been previously studied include oregano, thyme, lemon, sweet orange, grapefruit, and rosemary [ 42 , 43 ]. However, there are no current studies on the effectiveness of EOCa against HAV.…”
Section: Resultsmentioning
confidence: 99%
“…The chemical components of the EOs and especially the main compounds played as the main mediators in their pharmaceutical and biological activities [ 8 ]. The present results revealed that the bark EO has moderate to weak antiviral potentialities, especially against the two viruses, HAV and HSV1.…”
Section: Resultsmentioning
confidence: 99%
“…The hepatitis A virus (HAV) is one of the causes of more than a million infections around the world every year. This virus is a liver-self-limiting and sometimes life-threatening disease [ 8 ]. HAV infections were primarily caused by foods and water, as well as direct contact with an infected person [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation